Thai Computer Studies Student Teacher Complex Problem-Solving Skills Development: A Cooperative Learning Management Model - Sermsri, Natchanun; Sukkamart, Aukkapong; Kantathanawat, Thiyaporn (My University, 2022)
The research aim was to develop cooperative learning management (CLM) model using computational thinking (CT) and mind mapping techniques to promote Thai computer studies student-teacher (CSST) complex problem-solving skills (CPSS). The sample was 15 first-year CSSTs in the Faculty of Education's Computer Studies Department of Thailand's Thonburi Rajabhat University. The pre-study achievement test classified students into three levels (weak, moderate, or strong). Five experts were involved in the assessment of the CLM plan, which was determined to have a content validity index (CVI) at the highest level (mean = 4.00). They also evaluated the 21 indicator rubric scoring-type test tool for complex problem-solving skills (CPSS) and determined its CVI mean = 3.99. After a pilot test of 30 student teachers, a 42-item questionnaire was finalized. The final CPSS course involved five primary components within an eight-step process. The CSST used six sessions of four hours each. Results showed that the final course post-test score was 90.40 for all 15 student-teachers, significantly higher than the 70% achievement level setting.
Keywords: computer programming; information communications technology (ICT); pre-service teachers; Thailand